KINERJA TENAGA KESEHATAN RSUD DR. WAHIDIN SUDIRO HUSODO KOTA MOJOKERTO - Azizah Fitriani; Anisa Yuliani; Indra Krishernawan (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2022)
The purpose of this research is to evaluate the impact of occupational health and safety, compensation and work discipline on the performance of health workers in RSUD Dr. Wahidin Sudiro Husodo the city of Mojokerto. This study uses a quantitative approach. The data used is primary data sourced from questionnaires distributed to 71 health workers as respondents. The analyzer uses Multiple Linear Regression. From the results of the analysis it was found that OSH and work discipline contributed to changes in the performance of health workers. However, compensation has no significant effect on the performance of health workers.